Study of Mental Health Quotes for Positive Mindset in Digital Era - Pulungan, Husniah Ramadhani; Saputri, Nor Mita Ika (Bulletin of Science Education, 2023)
The purpose of this research is to examine mental health quotes for a positive mindset after the Covid-19 pandemic hit especially in digital era. The research method used is descriptive qualitative. The data source is 65 quotes from World Health Mental Day 2022, Make Mental Health for All A Global Priority on a very large banner. Data collection techniques include library techniques, see, and record. The analysis is qualitative content analysis. The presentation is descriptive and argumentative. The results of the study show that when someone wants to give quotes that aim to create a positive mindset, the tendency for the type of language style that appears consists of: Association 50%, Paradox 17%, Climax 15%, Allegory 8%, Anticlimax 6%, Irony and Rhetorical 2% each. The findings from this study are in the form of association style patterns with criticism, conditions, affection, prohibitions, definitive, optimistic, and advice patterns. The pattern of Paradox language style is patterned as suggestion, alert, prohibition, annoyance, consistency, and introspection. Command and support patterned Climax language styles. Allegory style pattern with an optimistic pattern. Anticlimax stylized pattern with prohibition pattern. Irony language style pattern which is patterned as a prohibition for satire. The patterned Rhetorical style of language asks something. Thus, the novelty revealed of the synergy from the fields of linguistics and counseling can produce more specific, effective, and efficient counseling therapies in the future, especially in mental health. Keywords: Digital Mental Health, Positive Mindset, Language Style